More on Hurwitz and Tasoev Continued Fractions - Komatsu, Takao (Sarajevo Journal of Mathematics, 2024)
Several new types of Hurwitz continued fractions have been studied. Most basic Hurwitz continued fractions can be expressed by using confluent hypergeometric functions _0F_1(;c;z). This expression enables us to find some more general Hurwitz continued fractions. A contrast between Tasoev continued fractions and Hurwitz ones yields some more general Tasoev continued fractions. Some Ramanujan continued fractions are also discussed. 1991 Mathematics Subject Classification. 11A55, 11J70, 11Y16, 33C10